Inhibition of MAPKs, Myc/Max, NFÎºB, and hypoxia pathways by phyllanthus prevents proliferation, metastasis and angiogenesis in Human Melanoma (MeWo) cancer cell line - Tang, Yin-Quan; Jaganath, I.B.; Manikam, R.; Sekaran, S.D. (Ivyspring International Publisher, 2014)
Background: Melanoma is the most fatal form of skin cancer. Different signalling pathways and proteins will be differentially expressed to pace with the tumour growth. Thus, these signalling molecules and proteins are become potential targets to halt the progression of cancer. The present works were attempted to investigate the underlying molecular mechanisms of anticancer effects of Phyllanthus (P.amarus, P.niruri, P.urinaria and P.watsonii) on skin melanoma, MeWo cells. Methods: The ten cancer-related pathways reporter array was performed by transfection of plasmid construct of transcription factor-responsive reporter of each pathway in MeWo cells. The affected pathways in MeWo cells after treatment of Phyllanthus extracts were determined using luciferase assay. Western blot, 2D gel electrophoresis and mass spectrometry analysis were performed to identity and confirm the affected proteins and signalling molecules in treated cells. Results: The ten-pathway reporter array revealed five different cancer-related signalling pathways were altered by Phyllanthus species in MeWo cells; NFÎºB, Myc/Max, Hypoxia, MAPK/ERK and MAPK/JNK (p<0.05). Western blot revealed that their intracellular signalling molecules including pan-Ras, c-Raf, RSK, phospho-Elk1, c-myc, Akt, HIF-1Î±, Bcl-2, and VEGF were down-regulated with concurrent of up-regulation; Bax, phospho-JNK-1/2 and phospho-GSK3Î², in MeWo cells upon Phyllanthus treatment (p<0.05). Proteomics-based approach was performed and MS/MS results revealed that 52 differential expressed proteins were identified (p<0.05) and involved in tumour growth, metastasis, apoptosis, glycogenesis and glycolysis, angiogenesis, protein synthesis and energy metabolism. Conclusion: This study provides insight into the regulation on multiple survival signalling pathways by Phyllanthus in melanoma and might be a therapeutic target for cancer treatment.